Short-Term Effects of Manual Therapy on Balance: A Multicenter, Randomized, Double-Blind Controlled Trial - Espí-López, Gemma V; Pavlu, Dagmar; Arnal-Gómez, Anna; Muñoz-Gómez, Elena; Martinez-Millana, Antonio; Marqués-Sulé, Elena (Journal of manipulative and physiological therapeutics, 2023)
OBJECTIVE: The purpose of this study was to analyze short-term changes in dynamic and static balance after a manual therapy protocol in healthy participants and analyze any repercussions on mood and perception of change after applying articulatory techniques. METHODS: A single-blind, randomized, multicenter clinical trial was conducted. Participants were allocated to either a manual therapy group (MTG) (n = 101) or a control group (CG) without intervention (n = 99), and measures were taken before treatment, after the intervention, and 1 week after treatment. Assessments included the Star Excursion Balance Test, Unipedal Stance Test (UPST), Profile of Mood States (POMS), and Patient Global Impression of Change (PGIC) scale. RESULTS: Two hundred healthy participants completed the study (mean age, 22 [SD = 2.67]). There was a statistically significant interaction between groups and time measurements in the right leg for anterior (P = .003), posteromedial (P < .001), and posterolateral (P = .001) directions in favor of the MTG, as well as in the left leg for anterior (P < .001), posteromedial (P < .001), and posterolateral (P = .012) directions. The analysis failed to show statistically significant interactions between any of the factors for the UPST and POMS (P > .05). The MTG showed a significant improvement compared to the CG after treatment (P = .003) and at 1-week follow-up (P < .001) on the PGIC scale. CONCLUSION: The results suggest the MT intervention was effective on dynamic balance in post-intervention in healthy participants, and some of the directions maintained the results at 1-week follow-up. Perception of change in post-treatment and 1-week follow-up also significantly improved. The protocol did not seem to produce changes in static balance and mood states. Positive changes after manual therapy were maintained in the short term.
Keywords: jednoduchá slepá metoda; Young Adult; techniky fyzikální terapie; Postural Balance; posturální rovnováha; Musculoskeletal Manipulations; dvojitá slepá metoda; Adult; Physical Therapy Modalities; Single-Blind Method; dospělí; lidé; Double-Blind Method; Humans; mladý dospělý; muskuloskeletální manipulace